Respuesta :
[tex]\bold{\huge{\underline{ Solution }}}[/tex]
Given :-
- Anjali has two sons
- One son is exactly 2 years older than the other
- At present, Anjali age is equal to the sum of the squares of the ages of her sons
- 6 years later, Anjali age will be 8 times the present age of the elder son
To Find :-
- We have to find the present ages of the Anjali and his sons
Let's Begin :-
Let the present age of the younger son be x
Elder son is exactly 2 years older than younger son
Therefore,
- The age of elder son is x + 2
According to the question,
The age of Anjali is equal to the sum of the squares of the ages of her sons
That is
[tex]\sf{ = x^{2} + ( x + 2)^{2}}[/tex]
[tex]\sf{ = x^{2} + x^{2} + 4 + 2x }[/tex]
[tex]\sf{ = 2x^{2} + 4x + 4 }[/tex]
Now,
We have to find the age of mother and her sons after 6 years
After 6 years
The age of the younger son
[tex]\sf{ = (x + 6)\: years }[/tex]
Therefore ,
The age of elder son
[tex]\sf{ = (x + 2) + 6 }[/tex]
[tex]\sf{ = x + 2 + 6 }[/tex]
[tex]\sf{ = x + 8 \: years }[/tex]
Here, It is given that,
- After 6 years the age of Anjali will be 8 times his elder son's age
That is,
[tex]\sf{ = 2x^{2} + 4x + 4 + 6 = 8( x + 8)}[/tex]
[tex]\sf{ = 2(x^{2} + 2x + 2 + 3) = 8(x + 2)}[/tex]
[tex]\sf{ = x^{2} + 2x + 2 + 3 = 4(x + 2)}[/tex]
[tex]\sf{ = x^{2} + 2x + 5 = 4x + 8}[/tex]
[tex]\sf{ = x^{2} + 2x - 4x = 8 - 5}[/tex]
[tex]\sf{ = x^{2} - 2x = 3 }[/tex]
[tex]\sf{ = x^{2} - 2x - 3 = 0 }[/tex]
By factorization method
[tex]\sf{ =(x + 1)( x -3 )}[/tex]
[tex]\sf{ = ( x = -1 ) or ( x = 3 )}[/tex]
- Age of the person can never be negative
Thus, The present age of the younger son is 3 years
Therefore,
Age of the elder brother
[tex]\sf{ = 3 + 2}[/tex]
[tex]\bold{ = 5 \: years}[/tex]
Present age of Anjali
[tex]\sf{ = 2(3)^{2} + 4(3) + 4 }[/tex]
[tex]\sf{ = 2(9) + 12 + 4 }[/tex]
[tex]\sf{ = 18 + 16 }[/tex]
[tex]\bold{ = 34\: years }[/tex]
Hence, The present age of Anjali and his two sons is 34 years, 5 years and 3 years .